A Bibliometric Study of Issues in Educational Policy - Sarı, Tamer; Aypay, Ahmet (Education sciences, 2024)
Education policies help to improve society by decreasing inequities and establishing effective learning environments. Periodic assessments can help researchers and policymakers uncover new obstacles and ensure progress on these ever-changing education policy concerns using critical theory. Bibliometric studies, a type of periodic study, emphasize the importance of data-driven approaches in the formulation and implementation of education policies. This study conducts a bibliometric analysis of education policy issues from 2000 to 2023. Based on keywords, we initially selected 931 articles from the Web of Science (WoS) database. Only articles in English were included, and we used PRISMA guidelines to reduce the number of articles to 363. We focused on citations, publication frequency, topics, trends, and issues. Two independent researchers analyzed the documents for reliability. For validity, we used transferability. We also used a content analysis of frequently cited articles. Our analysis revealed three prominent trends. The first trend pertained to controversial environmental issues and sustainability concepts in education policy. The second theme was professional development, special education, and school choice. The third one was science, vocational education, special education, and ICT. The content analysis results indicated that teaching and learning, professional development, science education, subject matter teaching, and mobile learning were the topics of the content analyzed articles. We found that relying solely on bibliometric review resulted in broad conceptualizations of educational policy issues, focusing primarily on efficiency and effectiveness. Additionally, we applied critical theoretical frameworks to conduct a more comprehensive analysis of the emergent issues identified through bibliometric analysis.